Human Resource Management in a Company Based on Human Values (Universitas Pamulang, 2025)
Human Resource Management is planning, organizing, implementing and controlling human resources in an organization to achieve goals effectively and efficiently. Especially if its implementation is based on human values. The problem of assessment is closely related to the problem of the structure of the sciences of human activity and human relations. In today's market-led economy, material well-being seems to trump all measures of human performance. In a blind attempt to achieve economic progress, there are times when managers compromise with human values. This, if not controlled at this stage, can lead to a lot of social inequality. Pancasila values, for example: justice, mutual cooperation, deliberation, the presence of law and unity in working together to achieve common goals. This type of research brings qualitative approaches to library study methods and data collection techniques by taking sources from e-book journals and internet media. By building human resources with character based on Pancasila values, Indonesia can create a generation that is moral and appreciates diversity